2017
DOI: 10.1093/icvts/ivw347
|View full text |Cite
|
Sign up to set email alerts
|

A simple preoperative score including the surgeon's experience to predict the probability of a successful mitral valve repair

Abstract: Preoperative assessment of seven variables can accurately predict the risk of an unsuccessful MV repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…From the valvular heart disease point of view, MAC has been associated with both mitral stenosis and regurgitation in observational studies, likely related to a combination of leaflet restriction, chordal traction, annular distortion, incomplete coaptation, and risk of endocarditis 4,43,44 . MAC adds complexity for the intention to surgically repair the mitral valve, and we found its presence to be highly associated with the need to replace the mitral valve in two studies 15,29 . Surgical strategies to deal with severe MAC may sometimes be necessary, such as mitral annular decalcification and reconstruction, periannular deep suture placement, left atrial to ventricular conduit, and intra‐atrial prosthesis placement 2,45 .…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…From the valvular heart disease point of view, MAC has been associated with both mitral stenosis and regurgitation in observational studies, likely related to a combination of leaflet restriction, chordal traction, annular distortion, incomplete coaptation, and risk of endocarditis 4,43,44 . MAC adds complexity for the intention to surgically repair the mitral valve, and we found its presence to be highly associated with the need to replace the mitral valve in two studies 15,29 . Surgical strategies to deal with severe MAC may sometimes be necessary, such as mitral annular decalcification and reconstruction, periannular deep suture placement, left atrial to ventricular conduit, and intra‐atrial prosthesis placement 2,45 .…”
Section: Discussionmentioning
confidence: 72%
“…Literature search and disposition of studies results are listed in Figure 1. There were 799 records identified from database search after duplicates were removed, and after screening the abstract 122 full‐text articles were evaluated and 26 studies were eventually included in our the quantitative meta‐analysis totaling 35 070 subjects 6‐31 . Characteristics of included studies are shown in Table 1, published between 1992 and 2017.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations